Molecular glue triggers degradation of PHGDH by enhancing the interaction between DDB1 and PHGDH - Ziqi Huang; Kun Zhang; Yurui Jiang; Mengmeng Wang; Mei Li; Yuda Guo; Ruolin Gao; Ning Li; Chenyang Wang; Jia Chen; Jiefu Wang; Ning Liu; et al. (Elsevier, 2024)
Cancer stem cells (CSCs) play a pivotal role in tumor initiation, proliferation, metastasis, drug resistance, and recurrence. Consequently, targeting CSCs has emerged as a promising avenue for cancer therapy. Recently, 3-phosphoglycerate dehydrogenase (PHGDH) has been identified as being intricately associated with the regulation of numerous cancer stem cells. Yet, reports detailing the functional regulators of PHGDH that can mitigate the stemness across cancer types are limited. In this study, the novel "molecular glue" LXH-3-71 was identified, and it robustly induced degradation of PHGDH, thereby modulating the stemness of colorectal cancer cells (CRCs) both in vitro and in vivo. Remarkably, LXH-3-71 was observed to form a dynamic chimera, between PHGDH and the DDB1-CRL E3 ligase. These insights not only elucidate the anti-CSCs mechanism of the lead compound but also suggest that degradation of PHGDH may be a more viable therapeutic strategy than the development of PHGDH inhibitors. Additionally, compound LXH-3-71 was leveraged as a novel ligand for the DDB1-CRL E3 ligase, facilitating the development of new PROTAC molecules targeting EGFR and CDK4 degradation.